2014
DOI: 10.5888/pcd11.130415
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Estimates of Gestational Diabetes Mellitus in the United States, Pregnancy Risk Assessment Monitoring System (PRAMS), 2007–2010

Abstract: IntroductionThe true prevalence of gestational diabetes mellitus (GDM) is unknown. The objective of this study was 1) to provide the most current GDM prevalence reported on the birth certificate and the Pregnancy Risk Assessment Monitoring System (PRAMS) questionnaire and 2) to compare GDM prevalence from PRAMS across 2007–2008 and 2009–2010.MethodsWe examined 2010 GDM prevalence reported on birth certificate or PRAMS questionnaire and concordance between the sources. We included 16 states that adopted the 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
338
5
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(364 citation statements)
references
References 26 publications
18
338
5
3
Order By: Relevance
“…Nearly 20%-40% of pregnancies are complicated by adverse intrauterine conditions, including maternal mental health disorders, diabetes, obesity, and preeclampsia (Ananth et al, 2013;Bennett et al, 2004;Dawson et al, 2015;DeSisto et al, 2014;Goodman et al, 2014;Rubertsson et al, 2014). These fetal exposures are significant risk factors for neuropsychiatric disease predisposition, in particular in male offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly 20%-40% of pregnancies are complicated by adverse intrauterine conditions, including maternal mental health disorders, diabetes, obesity, and preeclampsia (Ananth et al, 2013;Bennett et al, 2004;Dawson et al, 2015;DeSisto et al, 2014;Goodman et al, 2014;Rubertsson et al, 2014). These fetal exposures are significant risk factors for neuropsychiatric disease predisposition, in particular in male offspring.…”
Section: Resultsmentioning
confidence: 99%
“…the United States, 5%-17% are complicated by gestational diabetes, [4][5][6][7] and 6%-8% by one or more hypertensive disorders of pregnancy. [8][9][10] The prevalence of gestational diabetes, 4 gestational hypertension, and preeclampsia 4,[10][11][12] have increased, particularly in younger women.…”
Section: In 2008 Inmentioning
confidence: 99%
“…5,11,39,48 We assessed effect modification by age by testing an age*pregnancy complication interaction term based on a dichotomized age variable derived from the exploratory analysis, and by describing a stratified analysis by age ‡25 versus age <25 years.…”
Section: Additional Analysismentioning
confidence: 99%
“…The excess insulin in the infant body may further cause risk of obesity during the childhood and thereby result in type 2 diabetes during adult. In the 2015 analysis, the centres for disease control and prevention found that the occurrence of gestational diabetes is very high in the range of 9.4% [15].…”
Section: Type 2 Dmmentioning
confidence: 99%